Web information systems engineering - WISE 2014 : 15th International Conference, Thessaloniki, Greece, October 12-14, 2014, Proceedings, Part I - Bestavros, Azer; Manolopoulos, Yannis; Vakali, Athena; Zhang, Yanchun; Benatallah, Boualem (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the 15th International Conference on Web Information Systems Engineering, WISE 2014, held in Thessaloniki, Greece, in October 2014. The 52 full papers, 16 short and 14 poster papers, presented in the two-volume proceedings LNCS 8786 and 8787 were carefully reviewed and selected from 196 submissions. They are organized in topical sections named: Web mining, modeling and classification; Web querying and searching; Web recommendation and personalization; semantic Web; social online networks; software architectures amd platforms; Web technologies and frameworks; Web innovation and applications; and challenge.